Expression of STAT5, COX-2 and PIAS3 in Correlation with NSCLC Histhopathological Features - Pastuszak-Lewandoska, Dorota (Public Library of Science, 2014)
Signal transducers and activators of transcription (STATs), their inhibitors and cyclooxygenase-2 (COX-2) participate in transformations of many various types of cancers. The aim of the present study was to evaluate the relationship between STAT5A/B, COX-2, and PIAS3 mRNA expression and tumor staging, metastasis status, and histopathological subtype in 71 patients with confirmed non-small cell lung cancer (NSCLC) diagnosis. Total RNA was isolated from NSCLC tissue samples and the expression of the studied genes was assessed using TaqMan probes in real-time PCR assay. The expression levels of STAT5A, STAT5B, and COX-2 genes were increased in 69%, 79%, and 71% NSCLC samples respectively, while PIAS3 expression was decreased in the majority (69%) of the studied tissues. Statistically significant differences were observed between STAT5 isoforms (P = 0.0008), with higher expression of STAT5B. We found statistically significant positive correlation between STAT5B and COX-2 (rho = 0.045), and significant negative correlation between STAT5B and PIAS3 (rho = −0.049). The negative correlation between STAT5B and PIAS3 (rho = −0.43) was also observed in T2a+T2b tumor group. Additionally, STAT5B and COX-2 expression levels were significantly different between T1a+T1b and T2a+T2b tumors (P = 0.002 and P = 0.041, respectively), with higher expression of both genes in T2 tumor stage. PIAS3 expression was significantly lower in NSCC subtype as compared with SCC subtype (P = 0.017). Also, STAT5A and STAT5B immunoexpression was assessed, and the results indicated significantly higher protein levels in NSCLC patients as compared with controls (P = 0.048 and P = 0.034, respectively). High STAT5B immunoexpression was positively correlated with STAT5B gene expression in tumors (rho = 0.755). STAT5B protein level was also significantly higher in T2a+T2b tumors, reflecting high STAT5B gene expression in this group. There was no statistically significant association between mRNA and protein expression levels of the studied genes and patients' characteristics: age, gender, smoking. The obtained results highlight the importance of the genes STAT5B and COX-2 in lung cancer progression.